VALUATION OF STOCK VALUE WITH RELATIVE VALUATION AND ABSOLUTE VALUATION APPROACH IN BANKING SECTOR AT LQ 45 PERIOD 2015-2020 - Ferdinand, Ferry Vincenttius; Hulu, Edison; Ugut, Gracia Shinta S.; Sembel, Roy (ULTIMA InfoSys, 2024)
Investment in Indonesia during the COVID-19 pandemic increased. One of the significant and good indices in describing the condition of stocks in Indonesia is LQ45. Dlaam LQ45 The largest market capitalists are held by the financial sector Specifically the bank subsector therefore it needs to be further researched regarding these stocks. One of the interesting things is whether these stocks deserve to be considered a good investment instrument. One of the efforts to assess investment instruments is through the valuation stage. The valuation method used there are two, namely relative valuation with price to book value benchmarks and price earnings ratio and absolute valuation with dividend growth model method and some modifications of the model. From the results obtained, the recommendation of the position of the four financial stocks in LQ45 varies depending on the valuation technique used. On this basis, it can be said that it is important to know, know, and ethically the valuation techniques used are appropriate, good, and correct.